1996
DOI: 10.1002/ardp.19963290107
|View full text |Cite
|
Sign up to set email alerts
|

The Anti‐inflammatory Activity of N‐Substituted Indazolones in Mice

Abstract: N-Substituted indazolones were shown to be potent anti-inflammatory and analgesic agents in mice at 8 mg/kg. In addition, the agents were able to protect against death caused by endotoxins similar to those found in chronic infections. In part, the ability of these agents to suppress the inflammatory process is due to their blockage of cytokine release, e.g.TNF alpha and IL-1, as well as their inhibition of high affinity binding to receptors on target cells of inflammation. Suppressing these receptors can be li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…[2][3][4][5][6] Among a large variety of nitrogencontaining heterocyclic compounds, heterocycles containing a bridgehead hydrazine functionality have received considerable attention because of their pharmacological properties and clinical applications. [7][8][9][10][11][12][13][14][15][16][17][18][19] For example, 1-hydroxy-, 1-amino-and 1-hydrazino-2,3-dihydro-1H-pyrazolo[1,2-a]pyridazine-5,8-diones 1 were reported to possess anti-inflammatory, analgesic, anti-hypoxic and anti-pyretic properties. 19 Furthermore, pyrazolidine compounds have been converted into azaproline amino acids, which have been studied upon incorporation into traditional peptides as well as small molecule peptidomimetics 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Among a large variety of nitrogencontaining heterocyclic compounds, heterocycles containing a bridgehead hydrazine functionality have received considerable attention because of their pharmacological properties and clinical applications. [7][8][9][10][11][12][13][14][15][16][17][18][19] For example, 1-hydroxy-, 1-amino-and 1-hydrazino-2,3-dihydro-1H-pyrazolo[1,2-a]pyridazine-5,8-diones 1 were reported to possess anti-inflammatory, analgesic, anti-hypoxic and anti-pyretic properties. 19 Furthermore, pyrazolidine compounds have been converted into azaproline amino acids, which have been studied upon incorporation into traditional peptides as well as small molecule peptidomimetics 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic imides [1][2][3], -, 13-and y-alkylaminopropiophenones [4], amine-carboxyboranes and their metal complexes [5,6], thiosemicarbazones and their metal complexes [7], and triazolidinedione derivatives [8] have previously been shown to be potent anti-inflammatory and analgesic agents in rodents. These low molecular weight agents like other non-steroidal anti-inflammatory agents were able to block lysosomal hydrolytic and proteolytic enzyme activities as well as the synthesis of prostaglandins and leukotrienes, chemical mediators of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Indazolones [1] attract attention by their biological activities ( Figure 1), and their heterocyclic skeleton was found in anti-inflammatory agents, [2] 5-lipoxygenase inhibitors, [3] hypolipidemic agents (N 2 -h-butylindazolone) [4] or antitumora gentsi nh uman tumor cells. [5] Until recently,f our synthetic routes fori ndazolones were known as shown in Scheme 1(a-d).…”
mentioning
confidence: 99%
“…Indazolones are attractive heterocyclic compoundsp ossessing high bioactivities. [2][3][4][5] Therefore,w es elected 28 compounds in 100 mm and subjected them to preliminarys creening for anticancera ctivitiesi nH ela (human cervical cancerc ell), EJ and MDA-MB-231, MCF-7 (human breastc ancer cell), PC-3 andU 87. Using CCK-8 assay,i tw as shown that compounds 3a, 3c, 3d, 3f, 3i, 3q and 4e can lower the viability of cancerous cell line such as Hela, MCF-7 and U87 as showni nF igure 2.…”
mentioning
confidence: 99%